Feasibility study of a non-destructive fruit maturity testing system utilising capacitive properties - Mohammad Fuad Md Nor (Universiti Malaysia Perlis, 2008)
The classification for the maturity of fruits is not easily determined. This is especially true, for some fruits whose color have no direct correlation with to its level of maturity or ripeness. The levels of maturity can be determined by human expert, however for larger quantity inspection, this method is not practical. Therefore, accurate automatic classification for fruit maturity may be advantageous for the agriculture industry. In addition, consumers in supermarkets may also benefit from this system. This project is a feasibility study of nondestructive fruit maturity determination system based on capacitive properties. For this study, banana was chosen because it is easy to identify its maturity level by just looking to its color and ease of availability. Hence the data can be collected without destroying the fruit. The parallelplate capacitor was employed to determine capacitance of different levels of fruit maturity. Finally, Lab VEW 7.0 is a software tool was used to display data such as voltage and classify the samples for two types of maturity levels; under-ripe and ripe maturity level.